2022
DOI: 10.1016/j.jpsychires.2021.12.030
|View full text |Cite
|
Sign up to set email alerts
|

The role of social support and resilience in the mental health impact of the COVID-19 pandemic among healthcare workers in Spain

Abstract: Background Healthcare workers (HCWs) from COVID-19 pandemic hotspots across the globe have reported mental health problems, including anxiety, depression, or sleep problems. Many studies have focused on identifying modifiable risk factors, such as being afraid of getting infected or reporting shortage of personal protective equipment, but none have explored the role of protective factors. Method This cross-sectional study used an online survey to describe the associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 38 publications
3
34
0
5
Order By: Relevance
“…Even when the stressor is unmodifiable (e.g., living with an 80-year-old relative or vaccines not yet developed), psychological strategies can still modify mediational factors, such as fears or appraisal styles ( 51 , 52 ). At the interpersonal level , HCWs reported determinants across various problems, which is also in line with COVID-19 studies conducted among HCWs ( 53 , 54 ). Importantly, we found that perceived social isolation is a consequence of many reported problems.…”
Section: Discussionsupporting
confidence: 86%
“…Even when the stressor is unmodifiable (e.g., living with an 80-year-old relative or vaccines not yet developed), psychological strategies can still modify mediational factors, such as fears or appraisal styles ( 51 , 52 ). At the interpersonal level , HCWs reported determinants across various problems, which is also in line with COVID-19 studies conducted among HCWs ( 53 , 54 ). Importantly, we found that perceived social isolation is a consequence of many reported problems.…”
Section: Discussionsupporting
confidence: 86%
“…When adjusted for other factors, such as mental health, we did not find a direct significant association between resilience and pain-induced disability. Nevertheless, as reported previously, resilience is a protective factor against adverse psychological outcomes [ 74 , 75 ]. Resilience has been described as a predictor of coping with threats, and a predictor of mental well-being in people experiencing natural disasters and health crises [ 42 , 43 , 94 , 95 , 96 ].…”
Section: Discussionmentioning
confidence: 72%
“…In contrast, perceived social support related to the experience of pain showed no significant influence on pain-induced disability when it was adjusted for multiple potential predictors. Social support and resilience were acknowledged as protectors of mental health during the COVID-19 pandemic [ 19 , 74 , 75 , 76 ]. Taken together, these results suggest that social support may act as a mediator of pain-induced disability through resilience and mental health rather than an independent factor.…”
Section: Discussionmentioning
confidence: 99%
“…Research conducted previously explained that most people have difficulty maintaining physical and mental health conditions and have consequences experiencing psychological disorders such as depression, anxiety, severe stress, and fatigue during quarantine due to COVID-19 (24). Other risk factors identified were feeling unsupported, concerns about personal health, fear of carrying the infection and transmitting it to family members or others, isolation, feelings of uncertainty, and social stigmatization (25,26). Other studies supporting the research results stated several manifestations of helplessness experienced by COVID-19 sufferers, including emotional, motivational, and behavioural symptoms, which all decrease and affect a person's depression (10,27).…”
Section: Discussionmentioning
confidence: 99%